Correlation of the Indicators of High Performance Women Basketball Players' Game Characteristics with Physical Development and Physical Fitness - Rūtenis Paulauskas; Mindaugas Balčiūnas (Lithuanian Sports University, 2018)
Research  background  and  hypothesis.  Indicators  of  physical  fitness  and  physical  development  influence individual performance results.   Research aim was to identify correlation between basketball performance indicators and physical development and fitness. Research  methods.  The  basketball  players  (n  =  12)  of  the  Lithuanian  National  Women's  Basketball  Team were investigated. The performance indicators of this team were analyzed on the basis of data collected during the European Basketball Championship. During competition period the indicators of physical development and physical fitness of female basketball players were measured. Mathematical statistics methods were applied for the analysis of the research data. Pearson's correlation coefficients were applied to identify correlations among the indicators. Research  results.  The  correlations  of  the  number  of  blocks  with  height,  body  mass,  standing  reach  and psychomotor response were established. This indicator of game performance was technically simple and its efficiency was determined by good physical development and fast psychomotor reaction. The correlations of shooting percentage of different throws with physical fitness were different. Discussion and conclusions. The shooting percentage of 2-point field goals correlated with muscle mass, body mass and take-off duration. This allows suggesting that a certain number of shots are performed after the physical contact with an opponent and jumping faster during the moment of throw. No correlation was established between 3-point field goals, free throws and physical fitness indicators. This means that shooting percentage was influenced by other factors. Steals, turnovers and passes, as complex technical and tactical actions, did not correlate with the researched physical fitness indicators. Keywords: shot, jump, height, block, power.